Effects of Sex and Slaughter Weight on Physical Characteristics of Carcass of New Zealand White Crossbred - Haryoko, I; Warsiti, T (ANIMAL PRODUCTION, 2008)
The objective of the experiment was to investigate the effects of sex and slaughter weight on physical characteristics of carcass of New Zealand White crossbred rabbits.  32 heads of New Zealand White crossbred rabbits (16 male and 16 female) by individual cages were involved in this study.  Two levels of  nested classifications were applied in this study.  Male and female rabbits were grouped by slaughter weight (SW) SW1 (1,259.38 ± 16.44 g), SW2 (1,674.88 ± 26.55 g), SW3 (2,076.25 ± 26.59 g), and SW4 (2,398.50 ± 19.41 g), and four replications.  Variables consist of  carcass weight and percentage, lean, bone, and fat weight and percentages. Analysis of  variance and least significant test (LSD) were applied in this.  This study reavealed that sex did not affect significantly (P>0.05) in all variables, whereas slaughter weight had significant effect (P<0.01) on all variables measured.  It can be concluded that physical characteristics of carcass of male rabbits are similar to those of female with the same SW, but SW significantly increase physical carcass characteristics, except to percentage of bone. (Animal Production 10(2): 85-89 (2008) Key Words:  Rabbits, carcass characteristic, slaughter weight, sex, New Zealand White